2018
DOI: 10.1183/13993003.01886-2017
|View full text |Cite
|
Sign up to set email alerts
|

Macitentan in pulmonary hypertension due to left ventricular dysfunction

Abstract: The MELODY-1 study evaluated macitentan for pulmonary hypertension because of left heart disease (PH-LHD) in patients with combined post- and pre-capillary PH.63 patients with PH-LHD and diastolic pressure gradient ≥7 mmHg and pulmonary vascular resistance (PVR) >3WU were randomised to macitentan 10 mg (n=31) or placebo (n=32) for 12 weeks. The main end-point assessed a composite of significant fluid retention (weight gain ≥5% or ≥5 kg because of fluid overload or parenteral diuretic administration) or worseni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 25 publications
2
108
0
9
Order By: Relevance
“…Moreover, there are numerous examples of neutral studies in this area [2,3,8]. Recent examples include the ENABLE and MELODY-1 studies, showing that the two ERAs bosentan and macitentan failed to improve clinical measures or outcome in patients with HFrEF or HFpEF, respectively, and in both studies ERA therapy was associated with an increased occurrence of fluid retention [91,92]. In addition, the SIOVAC trial has shown that the use of sildenafil was associated with an increased risk of clinical deterioration and worse outcome versus placebo in patients with PH after VHD intervention (aortic, mitral, or tricuspid) [93], thus indicating that such therapies may even be harmful in the context of LHD.…”
Section: Targeted Pah Therapy In Ph-lhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are numerous examples of neutral studies in this area [2,3,8]. Recent examples include the ENABLE and MELODY-1 studies, showing that the two ERAs bosentan and macitentan failed to improve clinical measures or outcome in patients with HFrEF or HFpEF, respectively, and in both studies ERA therapy was associated with an increased occurrence of fluid retention [91,92]. In addition, the SIOVAC trial has shown that the use of sildenafil was associated with an increased risk of clinical deterioration and worse outcome versus placebo in patients with PH after VHD intervention (aortic, mitral, or tricuspid) [93], thus indicating that such therapies may even be harmful in the context of LHD.…”
Section: Targeted Pah Therapy In Ph-lhdmentioning
confidence: 99%
“…Furthermore, treatment discontinuations (due to side effects and/or lack of efficacy) were higher among patients with PH-HFpEF, with ERA less well tolerated than PDE-5 inhibitors. The MELODY-1 study, investigating the ERA macitentan, showed no benefit and significantly more edemas than placebo in patients with CpcPH [92]. This, together with the distinct tolerability of drug classes in patients with PH-HFpEF observed in COMPERA [7], may be indicative of differences with respect to efficacy and tolerability among targeted PH therapies in patients with LHD.…”
Section: Targeted Pah Therapy In Ph-lhdmentioning
confidence: 99%
“…This is different than left heart failure where endothelin-receptor blockade remains an active area of investigation, the pulmonary vasculature is not the primary problem, and results are less encouraging. 11 The MELODY-1 trial of endothelin-receptor blockade in individuals with significant pre-and post-capillary disease was recently published and did not suggest benefit. Instead, there was worse volume retention in treated individuals and no significant impact on pre-capillary parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, there was worse volume retention in treated individuals and no significant impact on pre-capillary parameters. 11,28 Some have speculated that endothelin-receptor blockade may be similar to beta-blockade where short-term worsening may be offset by long-term disease stability and improved mortality. 29−32 None of the participants in the current study are known to have pulmonary arterial hypertension, and our results spanning over a decade on average, suggesting that high levels of ET1 may prevent heart failure, cautiously argue against the idea that reduced ET1 levels or an ET1 blockade will lead to a long term benefit in the absence of pulmonary arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In the MELODY-1 trial, including 63 patients with Cpc-PH, macitentan showed numerically more frequent adverse events and fluid retention than did placebo and did not improve any exploratory endpoints (PVR, pulmonary capillary wedge pressure, cardiac index, and NT-pro-BNP), suggesting that macitentan may be harmful in WHO Group 2 PH as well. 46 Endothelin receptor antagonists and prostacyclin analogues have been studied in post-capillary PH. While short-term changes in haemodynamics have been seen, there has been either no clinical benefit or the suggestion for harm.…”
Section: Medical Interventionsmentioning
confidence: 99%